Euglycemic Ketoacidosis Induced by Low Carbohydrate Diet in a Non-diabetic Patient: A Case Report - Chang, Li-Yun; Lim, Lee-Moay; Chiu, Yi-Wen (Archives of Clinical and Medical Case Reports, 2020)
Low-carbohydrate diets are believed to work in reducing body weight. However, prolonged lacking of glucose intake can force body into keto-genesis, causing high anion gap metabolic acidosis. It is a rare condition in non-diabetic patients but we should keep high awareness on high risk populations especially chronic kidney patient since uremic status will complicate the detection of low carbohydrate diet associated ketoacidosis. <gdiv></gdiv>